2007
DOI: 10.1016/j.parint.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A long and winding road: The Plasmodium sporozoite's journey in the mammalian host

Abstract: The Plasmodium sporozoite, the infectious stage of the malaria parasite, makes a remarkable journey in its mammalian host. Here we review our current knowledge of the molecular and cellular basis of this journey, which begins in the skin and ends in the hepatocyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 88 publications
1
63
0
Order By: Relevance
“…These interactions would be expected to be driving forces in the selection for specific extracellular proteins that underpin recognition, adherence and response to target cells. For example, Plasmodium sporozoites interact with a diverse set of host tissues -firstly salivary gland tissue in the mosquito, and subsequently tropism to hepatocytes in the liver -utilizing receptor-mediated recognition of target cells (reviewed in Sinnis and Coppi, 2007). Alveolate recognition of the environment also includes positive and negative taxis in response to gradients of nutrients, toxins, light and gravity (Eckert, 1972;Fenchel and Finlay, 1984;Francis and Hennessey, 1995;Hemmersbach et al 1999;Selbach and Kuhlmann, 1999;Cadetti et al 2000;reviewed in Echevarria et al 2014), as well as avoidance interactions with predators (Knoll et al 1991;Hamel et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These interactions would be expected to be driving forces in the selection for specific extracellular proteins that underpin recognition, adherence and response to target cells. For example, Plasmodium sporozoites interact with a diverse set of host tissues -firstly salivary gland tissue in the mosquito, and subsequently tropism to hepatocytes in the liver -utilizing receptor-mediated recognition of target cells (reviewed in Sinnis and Coppi, 2007). Alveolate recognition of the environment also includes positive and negative taxis in response to gradients of nutrients, toxins, light and gravity (Eckert, 1972;Fenchel and Finlay, 1984;Francis and Hennessey, 1995;Hemmersbach et al 1999;Selbach and Kuhlmann, 1999;Cadetti et al 2000;reviewed in Echevarria et al 2014), as well as avoidance interactions with predators (Knoll et al 1991;Hamel et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Both immune individuals immunized with sporozoites and prophylactically treated with chloroquine and semiimmune patients from an area where malaria is endemic are able to recognize CSP, showing that anti-CSP immunity is necessary for protection (49). CSP binds to highly sulfated heparan sulfate proteoglycans (HSPG) on the surfaces of hepatocytes; this interaction is critical for cell invasion, arresting circulating sporozoites in the liver (45,50,51). Our heparan sulfate binding assay showed that the structural domains involved in such interactions are conserved in PvRMC-CSP.…”
Section: Discussionmentioning
confidence: 99%
“…Sporozoites must overcome natural barriers to reach their host/target cell (the hepatocyte), including circumventing the liver's sinusoidal barrier and Disse's space via Kupffer cells (Sinnis and Coppi 2007). Along with CSP, TRAP and SPECT 1 and 2, two new proteins have been recently described as they are directly involved in sporozoite cell-traversal and hepatic cell invasion: Cel-TOS and TRSP, respectively (Kaiser et al 2004b;Kariu et al 2006;Labaied et al 2007;Bergmann-Leitner et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…P. falciparum sporozoites (larvae-like structures) injected into the skin during the bite of an infected female Anopheles mosquito travel through the bloodstream to the liver during the first phase of human malaria infection where they cross the sinusoidal layer through Disse's space and Kupffer cells to invade their primary target: the hepatic cell (Sinnis and Coppi 2007). Two highly relevant proteins participating in such host-pathogen interactions have been widely studied: the circumsporozoite protein (CSP) and the thrombospondin-related anonymous protein (TRAP) (Akhouri et al 2008;Rathore et al 2003); both have been shown to mediate sporozoite motility, host-cell recognition, cell traversal, binding, and entry to host cells.…”
Section: Introductionmentioning
confidence: 99%